Growth performance of Magnolia elegans planted in restoration area of montane forest in Cameron Highland, Pahang - Che Wan Razaley, Che Wan Muhammad Hafiz (2018)
As the human population increases, deforestation rates and the emissions of carbon dioxide into the atmosphere also increase causing global warming. In Malaysia, there are many microclimates factors such as temperature and rainfall which growth may affect the performance of plants or trees and even human activities. The aim of this study is to monitor the growth performance of Magnolia elegans that was planted in restoration area in Cameron Highlands, which is located at the altitude of approximately 1330m above sea level. The trial plots were divided into 2 plots, Open-compacted and Secondary-vegetation. The growth parameters measured and analyzed were height, diameter and chlorophyll content. The result suggested that the planted species gave different rate of adaptation and growth according to the selected plot. Whereby the species planted in open-compacted plot grew significantly better compared to secondary-vegetation plot.